Modeling the Minho River plume intrusion into the Rias Baixas (NW Iberian Peninsula) - Sousa, M. C.
The Minho River discharge is recognized as particularly important in driving the circulation and hydrography of Rias Baixas, which are highly productive fishery and aquaculture regions extremely sensitive to environmental characteristics. The intrusion of the Minho River plume inside these Rias can reverse the normal circulation pattern and affect the macronutrient concentrations, imposing a control on new production within the estuarine environment. Consequently, detailed knowledge of the propagation of the plume in this zone facilitates largely the management of many exploited and protected local species. Thus, the main purpose of this work is to study the propagation and influence of Minho estuarine plume in Rias Baixas circulation and hydrography through the development and validation of an application of MOHID numerical model including a local coastal nesting configuration fed by Minho River discharge predicted by an estuary model. The nesting configuration and the Minho estuary model were validated and then applied to research the role of the wind and Minho River discharge effects on the circulation reversal. The spring of 1998 was chosen as the validation period for Minho estuarine plume propagation, considering there were field data available for this period confirming the intrusion of the Minho River plume in Rias Baixas and reversing the normal circulation pattern. Predictions replicate accurately the hydrodynamics and thermohaline patterns in Minho estuary and Rias Baixas under these conditions showing that the developed model application reproduces the dynamics of the coupled estuarine-near coastal systems under research. Results showed that a buoyancy intrusion caused by the Minho River reverses the normal estuarine salinity longitudinal gradient and estuarine circulation of the Rias de Vigo and Pontevedra. Moreover, it was found that a continuous moderate Minho River discharge combined with southerly winds is enough to reverse the Rias Baixas circulation pattern, reducing the importance of the occurrence of specific events of high runoff values.